Draft Annual Plan 1982-83 Volume V Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1981)
The State Industrial Development Corporation (SIDCO) is the nodal agency for promotion and development of industries in the Situation Within its strategy of Development electronics and precision engineering industries claim priority for its obvious .advantage to the State .Thought the with tuts, the accent is on the resource based industries Nature . provide with rich and varied endowments in the shape of mineral wealth, forests, temperate fruit high quality wool, skins, hides and furs, temperate climate and large and well spread out water resources. These endowments offer a big. future for industrial development. 25 studies are proposed to be undertaken during the Plan period for resource-based industries and electronics and precision engineering units.
Government of Jammu and Kashmir
Planning and Development Department Jammu
Keywords: Large and Medium Industries; Himalayan Wool combers; Tavi sectors; Directorate of Industries Counsels; Provision of Infrastructure; Project reports and identification of entrepreneurs; Technical and professional manpower development; Provision of -common facilities; Assistance in the matter of obtaining licenses; Provision of term loans and seed finance assistance; Arranging technology